GLP-1 RAs and Muscle Function Outcomes in Active Adults and Athletes - Świerczek, Anna; Bartosz Zawadzki; Natalia Kornacka; Jakub Zwardoń; Katarzyna Naja; Miłosz Rewekant; Aleksander Gajkowski; Tomasz Adam Szczepanowski; Krzysztof Bednarski; Zuzanna Walczak (Quality in Sport, 2026)
Background:Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) represent a rapidly expanding pharmacological class used in the management of obesity and type 2 diabetes mellitus. Although prior reviews have documented their effects on body composition and skeletal muscle mass, functional outcomes including muscle strength, gait performance, and cardiorespiratory fitness in physically active adults and recreational athletes remain insufficiently characterised. Objective: To systematically review and critically appraise current clinical evidence regarding the effects of GLP-1 RA therapy on muscle function outcomes — specifically handgrip strength, gait speed, and VO2max — in physically active adults and recreational athletes. Methods: A narrative review of peer-reviewed literature published between 2019 and 2026 was performed using PubMed, EMBASE, and Cochrane databases. Results: GLP-1 RAs consistently reduce skeletal muscle mass; however, functional outcomes show a more heterogeneous pattern. Handgrip strength is generally preserved or modestly reduced, gait speed remains largely unaffected, and VO2max may improve with concomitant exercise training. The physically active population is underrepresented in existing trials. Conclusions: GLP-1 RA therapy does not uniformly impair muscle function in physically active individuals. Exercise prescription should be integrated with pharmacotherapy to optimise functional outcomes. Further dedicated RCTs in athletic populations are warranted.